Design, Analysis and Implementation of Rectangular Variable Cross-section Pipe Film Placing Robots in Nuclear Power Plant - Zhang Pengfei; Wang Rui; Wu Jianrong (Jixie chuandong)
Based on the analysis of the inspection environment and requirements for nuclear power plant rectangular variable cross-section pipes, this study proposes a new design scheme of the film placing robot, introduces the structure and operating principle of the robot, analyzes the mechanical relationship between the output force of the robot supporting mechanism and the total weight, makes a prototype, and carries out the relevant experimental verification. The results show that the robot has strong adaptability to rectangular variable cross-section pipes, high positioning accuracy, and can meet the requirements of film placing in radiographic inspection.